2016
DOI: 10.14740/jocmr2789w
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Toxoplasma gondii Infection in Miners: A Case-Control Study in Rural Durango, Mexico

Abstract: Background: Very little is known about the seroepidemiology of infection with the parasite Toxoplasma gondii (T. gondii) in miners. We determine the association of T. gondii infection and the occupation of miner, and the association of seropositivity for T. gondii with the socio-demographic, clinical, work and behavioral characteristics of the miners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…gondii infection in the subset of people from rural areas observed in our present study might have contributed to an increase in the general seroprevalence. However, the seroprevalence found in people with alcohol consumption is lower than those found in other population groups in our region, including waste pickers (21.1%) [ 23 ], schizophrenic patients (20%) [ 24 ], inmates (21.1%) [ 25 ], or miners (60%) [ 26 ]. This relatively low seroprevalence found in our study coincides with the finding of a study of the Finnish general population, where researchers found that T .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…gondii infection in the subset of people from rural areas observed in our present study might have contributed to an increase in the general seroprevalence. However, the seroprevalence found in people with alcohol consumption is lower than those found in other population groups in our region, including waste pickers (21.1%) [ 23 ], schizophrenic patients (20%) [ 24 ], inmates (21.1%) [ 25 ], or miners (60%) [ 26 ]. This relatively low seroprevalence found in our study coincides with the finding of a study of the Finnish general population, where researchers found that T .…”
Section: Discussionmentioning
confidence: 77%
“…The questionnaire was used as a method for recording simple variables as age, gender, etc. The questionnaire has been used in a number of epidemiological studies in the same language in the same country [13,14,18,[21][22][23][24][25][26]. Items of housing variables were previously validated [27].…”
Section: Data Collection and Socio-demographic Clinical Behavioral And Housing Variables Of Participantsmentioning
confidence: 99%
“… 21 However, there are specific population groups in Mexico with a high seroprevalence of T. gondii infection; for instance, miners in Durango State who had a seroprevalence of 60%. 22 We looked for sociodemographic, behavioural and housing characteristics associated with T. gondii seropositivity. Logistic regression analysis showed that T. gondii infection was positively associated with availability of potable water at street, and negatively associated with being born in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the link between infection and boar meat consumption, our results are in line with those reported in previous studies in northern Mexico. We previously found an association between T. gondii infection and boar meat consumption in several populations in Durango State, Mexico, including miners [ 25 ], elderly people [ 26 ], patients with work accidents [ 27 ], and the general urban population [ 28 ]. The results thus indicate that boar meat consumption is an important factor for T. gondii infection in northern Mexico.…”
Section: Discussionmentioning
confidence: 99%